The Psychometric Properties of the Norwegian version of Youth Self Report (YSR) - Reedtz, Charlotte; Løvereide, Stine (PsykTestBarn, 2021)
Description: Youth Self Report (YSR) is one of the instruments in Achenbach´s System of Empirically Based Assessment (ASEBA), in addition to Child Behavior Checklist (CBCL) and Teacher´s Report Form (TRF). YSR assesses competence, level of adaption and behavioral difficulties within the age group of 11—18. YSR provides a total score, scores for internalizing and externalizing behavior, as well as scores for 8 different syndrome scales. In addition, a score for competencies is given. It takes 20 minutes to complete the form. The first manual was published in 1987. Torunn S. Nøvik and Sonja Heyerdahl (2002) have translated the questionnaire into Norwegian. The requirements for professionals utilizing the YSR consist of test-specific training, as well as recommendations for a master´s degree and experience from working with youth and families. Norwegian test forms are purchased online at aseba.nl. The ASEBA-forms are commonly used in municipal services, in specialized health care unites and in research. Literature search: Twenty-seven Norwegian and 23 Swedish/ Danish publications are included in this review. Only one publication is a specific psychometrical study. The remaining publications are studies where YSR is used to measure competencies, level of adaption and behavioral difficulties as an outcome variable, a control variable, or for descriptive purposes of the population. Twenty-one out of the 27 Norwegian publications are based on clinical samples (ex. premature babies, very low-birth weight, severe dyslexia, congenital heath defect or behavioral issues). Several of these samples had comparison- and control groups from general populations. Among the Swedish and Danish included publications, 7 out of the 23 studies had clinical samples, while the remaining studies were based on youth samples (12-17 years old) from schools in different Norwegian regions. Psychometrics: Eleven publications reported adequate results regarding YSR´s reliability, though only two norm-studies were based on Norwegian or Swedish/ Danish populations. The studies found that the test has high construct validity and may be used as an indicator of behavioral difficulties. YSR shows moderate to high correlations with similar tests regarding internalizing and/or externalizing difficulties. Conclusion: There is good evidence for YSR´s reliability based on Norwegian and Swedish/ Danish samples, and relatively good evidence for the test´s construct validity. Nevertheless, there are few Scandinavian studies that aim to develop norms and they rest upon small and/or 20-year-old samples, which is problematic for clinical use. More studies are needed to examine YSR´s psychometric properties for the Scandinavian population.